Pengalaman Komunikasi Orang Tua Terhadap Pendampingan Menggunakan Smartphone dan Internet - Sarah Veradinata Purba; Hedi Pudjo Santosa; M Bayu Widagdo; Primada Qurrota Ayun (Interaksi Online, 2016)
Smartphone and the internet is one of the new things that interest youngpeople nowadays especially among school age children. In the environmentalguidelines for schools, Smartphone and the internet have become mandatoryitems brought to be able to get along. This research aims to know thecommunication experience of parents in doing this against the use of Smartphoneand the internet. This study uses qualitative methods with phenomenologicalapproach. Informants in this study are the parents and children of 6 pairs. Theresults of this research were obtained that parents give the Smartphone andinternet facilities to the child because it wants his son to be able to get along andnot outdated. In addition to that of the research results are also obtained that thechild learns the internet the first time is from the experience of children see theirparents with internet and Smartphone, and the average child can already use theinternet since primary school. Mentoring is done by the parents the child'scommunication with disembodied here, where parents give advice – advice to thechild in the use of Smartphone and the internet